A Note on the Occurrence of Mango Thrips, Scirtothrips mangiferae Priesner (Thysanoptera: Thripidae), Infesting Mango Seedlings in Khartoum State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
Mango thrips, Scirtothrips mangiferae Priesner (Thysanoptera: Thripidae), isa major pest of mangoes. It feeds on young shoots and leaves causing leaf malformation,stunting of growth and premature drop of leaves. These symptoms were observed onmango seedlings in the nursery at Shambat Research Station, Khartoum State, Sudan,during season 2009/2010. Immature stages and adults specimens of the insect pest andphotographs of symptoms were sent to the Kuopio Natural History Museum, Finland, foridentification. The insect pest was identified as Scirtothrips mangiferae Priesner. This isthe first report of Scirtothrips mangiferae in Sudan